Inovasi Pembelajaran Untuk Anak Usia Dini Dalam Merdeka Belajar Di Era Society 5.0 - Shofiyatuz Zahroh; Rif’atul Anita; Milla Ahmadia Apologia (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
The independent curriculum is the curriculum that is considered the most humanistic among the previous curricula. The birth of the independent curriculum is adapted to current developments which have entered the era of society 5.0, where technology is very closely linked to the lives of every individual at any age, from birth to the elderly. Therefore, the learning process must also undergo changes, by innovating each lesson. Based on this, it requires every educational institution to develop the potential of each human resource. Therefore, the aim of this community service is to facilitate early childhood educators throughout the world to develop their potential in making innovations in learning according to children's current needs. The final result of this PkM is that all educators in the early childhood education unit receive information or curriculum updates, and are able to innovate the independent curriculum in accordance with the culture of their respective school environments.